Anti-platelet drugs, pharmacogenomics and stent thrombosis: What’s new? - Benjamin, John (SA Heart Journal, 2017)
Stent thrombosis is a catastrophic complication of percutaneous coronary intervention (PCI) and is associated with a mortality of 25 to 40%. The perception that stent thrombosis is very low in all patients has resulted in a lack of adherence to professional guidelines. New data to identify patients at increased risk for stent thrombosis are emerging. Clopidogrel is a prodrug and the activation of clopidogrel is dependent on CY2C19. Numerous alleles of CYP2C19 exist. The allele CYP2CP*2 has been associated with a marked decrease in platelet responsiveness to clopidogrel. Heterozygote carriers of the CYP2C19*2 have a 2.7 fold increased risk and homozygotes a 4.8 fold increased risk of stent thrombosis. Prospective randomised clinical trials will be necessary to determine the efficacy of CYP2C19 genotype directed therapy in evidence-based clinical decision making. Point-of-care platelet-function tests are becoming available and some centres are now performing such tests on their PCI patients. The most recent AHA/ACC /SCAI guidelines recommend testing for clopidogrel responsiveness in patients at high risk of subacute stent thrombosis and recommend increasing the dose of clopidogrel in non-responders.